2013
DOI: 10.1364/ol.38.001479
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated Raman scattering imaging by continuous-wave laser excitation

Abstract: We demonstrate a low-cost-stimulated Raman scattering (SRS) microscope using continuous-wave (cw) lasers as excitation sources. A dual modulation scheme is used to remove the electronic background. The cw-SRS imaging of lipids in fatty liver is demonstrated by excitation of C─H stretch vibration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Recently, nonlinear optical microscopy imaging techniques such as stimulated Raman spectroscopy (SRS) and coherent anti-Stokes Raman scattering (CARS), have become powerful tools for label-free imaging in cells and tissues as they enable deep tissue imaging that is non-destructive, has biochemical specificity, and scalable resolution [5355]. Previous studies have demonstrated the potential of this approach to identify patients with gradually progressive fibrotic processes such as NAFLD [56], fatty liver disease (FLD) and cirrhosis [57].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, nonlinear optical microscopy imaging techniques such as stimulated Raman spectroscopy (SRS) and coherent anti-Stokes Raman scattering (CARS), have become powerful tools for label-free imaging in cells and tissues as they enable deep tissue imaging that is non-destructive, has biochemical specificity, and scalable resolution [5355]. Previous studies have demonstrated the potential of this approach to identify patients with gradually progressive fibrotic processes such as NAFLD [56], fatty liver disease (FLD) and cirrhosis [57].…”
Section: Resultsmentioning
confidence: 99%
“…For optimal noise rejection, signal and reference beam powers should be equal. In laser scanning microscopy, because the non-uniformity of the refractive index and stationary absorption in the sample cause the probe beam to vary in intensity during the sample scan, an auto-balanced photodetector is used to compensate for the intensity imbalance between the signal and reference beams [31,32]. However, the scan speed is limited by the response time of the autobalancing loop.…”
Section: Improvement In Snr By the Spatially Segmented Balanced Detecmentioning
confidence: 99%
“…The combinatorial power n is n ¼ 3 for CARS-type measurements and n ¼ 2 for SRStype experiments. Although CRS microscopy can, in principle, be carried out with cw lasers, 43 the use of pulsed excitation has the distinct advantage of providing high peak intensities while the average power of the incident light remains at tolerable levels. Equation (9) captures the growth of the overall signal if the pulse width τ is decreased.…”
Section: Light Sourcesmentioning
confidence: 99%